UMP and Hebei University, a decade together - Yong, Ying Mei (2021)
It has been a decade for Universiti Malaysia Pahang (UMP) to collaborate with Hebei Universitiy (HBU) since the establishment of Mandarin Language & Culture Centre (MLCC) in 2011. With the support of the Ministry of Higher Education (MOHE), Confucius Institute Headquarters (Hanban) and HBU, MLCC was upgraded to Confucius Institute in 2018.